The Influence of Career Development, Digital Leadership Style, and Work-Life Balance on Employee Job Satisfaction at PT. BPR BKK JATENG (PESERODA) Karanganyar Branch - Erlina Sih Rahayu; Yanita Hendarti; Ambyah Atas Aji; Muflik Malikun (International Journal of Economics and Management Sciences, 2024)
The purpose of this study was to analyze the influence of career development, digital leadership style, and work-life balance on employee job satisfaction in the banking sector, both partially and simultaneously. The population in this study were all employees of PT. BPR BKK Jateng (Peseroda) Karanganyar Branch, totaling 119 people. Because the population is relatively small and reachable, the entire population was sampled in this study using the total sampling technique. Data analysis techniques used include: Instrument testing (validity test and reliability test), Classical Assumption Test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test). To test the hypothesis, multiple linear regression analysis, t-test (Partial), F-test (Simultaneous), and Coefficient of Determination were used. The results of the analysis showed that the three independent variables, namely Career Development, Digital Leadership Style, and Work-Life Balance, had a significant influence on Job Satisfaction of PT. BPR BKK JATENG (PESERODA) Karanganyar Branch.